PECULIARITIES OF ADVERSE ENVIRONMENTAL EFFECTS’ MANIFESTATIONS IN AGRICULTURAL LANDSCAPES OF SOUTHEASTERN RAVINE STEPPE AND THE ROLE OF PROTECTIVE FOREST PLANTATIONS IN THEIR PREVENTION - Bila, Yu. M.; Tkach, L. I. (Forestry and Forest Melioration, 2018)
Introduction The nature of land resources use and agricultural production in the Luhansk region, as well as all over Ukraine, is not eligible for the formation of stable, ecologically balanced agricultural landscapes. This increases the area of degraded and unproductive soils, especially as a result of drought and erosion. So important is the assessment of systemic irregularities of environmental parameters of agrarian landscapes of the region and the development of appropriate agroforestry measures to leveling the negative impacts and create favorable conditions for the effective use of bioclimatic potential of arable lands. Materials and Methods The study of forest component of agricultural landscapes as a set of protective plantations of different spatial and target forms was carried out according to standard agroforestry techniques taking into account basic research and development and also modern regulatory and reference base objectively reproducing the existing ecological state of agricultural landscapes. Agricultural landscapes which are the typical by the land structure and environmental conditions, as well as reclamation stands of linear type and their systems, placed within the territorial limits of the landscapes, were used as the research objects. Results Recommended field-protective forest cover for the Lugansk region is 3.7 %, which is ecologically reasonable under current conditions and the existing structure of land. Calculations show that 16.4 thousand ha of field-protective stands should be created in addition to the existing 29.6 thousand ha of forest shelter belts. Thus the total area will be about 46 thousand ha and field-protective forest cover will reach the project one. The total forest cover percent will increase up to 17.7 % that will be an essential basis for improving the overall ecology of the region and its individual components. It is necessary to create 16.39 thousand ha of additional flow regulating forest belts on arable lands with the slope of ? 3° and 8.10 thousand ha on the lends with the slope of 3-7°, which will amount 24.49 thousand ha in total. The current status of other categories of land requires providing protection of grasslands and pastures located on slopes of more than 2° by 36.3 and 72.7 % of the total area, respectively. About 42.0 % of hayfields and over 68.5 % of pastures undergo water erosion, which significantly affects the soil fertility and productivity of grasslands. Conclusions Planting of forest reclamation complex play a dominant stabilizing role in agricultural landscapes formed on modern adaptive-landscape basis. The required amount of protective forest plantations is calculated at a regional level by taking into account local natural and man-made problems affecting the agricultural production. The proposed projected amounts of protective forest plantations of different spatial and target forms, based on a modern regulatory framework, are important to improve the spatial structure of modern agricultural landscapes.